空间的包含：庄子〈逍遥游〉“游”义 之探析 = The perspective of space: the philosophy of “you” in Zhuang Zi Xiao Yao You. - Tung, Crystal Kwai Jie. (2012)
The term „You‟ is not coined by Zhuang Zi although the frequency of use is rather heavy compared to other texts recorded during the Pre-Qin. „You‟ consists of several layers of meanings. Previous researchers have defined it as a form of sightseeing, or „You Xin‟ which is a form of freedom. Others interpreted „You‟ as a form of liberation to reach a state of transcendence. „You‟is also seen as one being in harmony with the nature. In fact, the philosophy of „You‟ in Zhuang Zi comprises not just the literature sense but a questioning of life pertaining issues. Beside, the concept on „You Yu Yi’ was recorded within Lun Yu, which had prompted some researchers to define the „You‟ seen in Confucian as a form of personality development. Thus, the author will seek to investigate the difference in „You‟ in between Taoism and Confucian.